2015
DOI: 10.1016/j.jbiomech.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics vs. inverse dynamics methods to determine passive drag in two breaststroke glide positions

Abstract: Computational fluid dynamics (CFD) plays an important role to quantify, understand and "observe" the water movements around the human body and its effects on drag (D). We aimed to investigate the flow effects around the swimmer and to compare the drag and drag coefficient (CD) values obtained from experiments (using cable velocimetry in a swimming pool) with those of CFD simulations for the two ventral gliding positions assumed during the breaststroke underwater cycle (with shoulders flexed and upper limbs ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
0
14
1
1
Order By: Relevance
“…Vilas-Boas et al (2010) noted a gliding speed in breaststroke of 1.37 m • s −1 after the push-off in national level swimmers. Costa et al (2015) assessed the push-off at speeds between 1.1 and 1.7 m • s −1 . Shahbazi, Sanders, McCabe and Adams (2007) reported that experienced swimmers show a speed after the tumble turn of 2.42 m • s −1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vilas-Boas et al (2010) noted a gliding speed in breaststroke of 1.37 m • s −1 after the push-off in national level swimmers. Costa et al (2015) assessed the push-off at speeds between 1.1 and 1.7 m • s −1 . Shahbazi, Sanders, McCabe and Adams (2007) reported that experienced swimmers show a speed after the tumble turn of 2.42 m • s −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Eventually, researchers started to investigate whether the different approaches would return the same results (i.e., goodness-of-fit), if they were sensitive enough to reflect the same phenomenon or not. It was reported that experimental data tend to overestimate the values in comparison to numerical simulations (Costa et al, 2015). Nevertheless, both CFD and experimental data were dependent on swimming velocity.…”
Section: Introductionmentioning
confidence: 91%
“…By modifying disk orientation and flow characteristics (constant or variable acceleration), they found that hand acceleration (from 2.84 to 5.84 m/s) strongly increased propulsive drag by up to 40%. Following this study, interest turned to evaluating water resistances during glide periods [54,[66][67][68][69]. Investigators scanned the swimmer's whole body and tested resistances as a function of position (arms extended at the front or along the body) and depth.…”
Section: Fluid Perturbations From Swimmer's Movementmentioning
confidence: 99%
“…The importance of the flow effects around the swimmer has been introduced by Costa et al (2015) wherein k-ε model of turbulence had been used to simulate fluid flow around the model and their results were validated with swimming pool experiments. Zhan (2015) in another research by using of 3D numerical simulation analysis evaluated passive drag near free surface by RNG k-ε turbulence model.…”
Section: Introductionmentioning
confidence: 99%